HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN INQUIRY LEARNING - Maryamah Maryamah; Erlina Rupaidah; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2016)
This research was motivated to know the difference of learning results of economy subject, as well as to know the comparison of the use of learning model of Problem Based Learning (PBL) and Inquiry. The method used in this research was experiments with comparative approach. The population in this research were all students of class X, amounting to 159 students with the sample was amounted to 77 students, by cluster random sampling. Data collection technique was using interview, documentation, and test. Hypothesis testing was using t-test of two independent samples and the n-gain effectiveness. Based on analysis of the data, it obtained the result that there is a difference in learning results of economy subject which taught by using learning model of Problem Based Learning (PBL) and Inquiry.Penelitian ini dilatar belakangi untuk mengetahui perbedaan hasil belajar ekonomi, serta untuk mengetahui perbandingan penggunaan model pembelajaran Problem Based Learning (PBL) dan Inquiry Learning. Metode yang digunakan dalam penelitian ini adalah eksperimen dengan pendekatan komparatif. Populasi dalam penelitian ini adalah seluruh siswa kelas X, berjumlah 159 siswa dengan sampel 77 siswa, yang ditentukan dengan cluster random sampling. Teknik pengumpulan data menggunakan wawancara, dokumentasi, dan tes. Pengujian hipotesis menggunakan t-test dua sampel independen dan n-gain efektivitas. Berdasarkan analisis data, diperoleh hasil bahwa ada perbedaan hasil belajar ekonomi yang diajarkan menggunakan model pembelajaran Problem Based Learning (PBL) dan Inquiry Learning.Kata kunci: hasil belajar ekonomi, problem based learning, inquiry learning